Cultural and Religious Interaction at Medana Cemetery: A Model of Social Harmony - Jayadi, Suparman; Adabiyah, Radiyatun (Universitas Andalas, 2024)
This research examines the cultural and religious interactions between Muslim and Hindu communities in Makam Medana, North Lombok, West Nusa Tenggara. Using a qualitative method with a case study approach, data was collected through direct observation, in-depth interviews, and document analysis with Fritjof Schuon's theory of social esotericism used as the basis for analysis. The results show that the Medana Tomb serves as an important space for social harmony, where both communities engage in shared spiritual and cultural practices. Through inner experiences that transcend religious, cultural and social boundaries, the tomb serves as a bridge that connects different religions through a universal understanding of divine truth that manifests in different outward forms. These interactions facilitate mutual understanding and respect, and contribute to the formation of an inclusive and harmonious society in North Lombok. This research concludes that Makam Medana offers a model of social harmony that is relevant in a multicultural context.